2017
DOI: 10.1111/cogs.12479
|View full text |Cite
|
Sign up to set email alerts
|

A Priori True and False Conditionals

Abstract: The theory of mental models postulates that meaning and knowledge can modulate the interpretation of conditionals. The theory's computer implementation implied that certain conditionals should be true or false without the need for evidence. Three experiments corroborated this prediction. In Experiment 1, nearly 500 participants evaluated 24 conditionals as true or false, and they justified their judgments by completing sentences of the form, It is impossible that A and ___ appropriately. In Experiment 2, parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 38 publications
0
40
1
2
Order By: Relevance
“…We corroborated the possibility table's assignments in the previous study in which the participants judged conditionals as true or false, and we evaluated each of the four cases in their partitions as possible or impossible (Quelhas et al., ). For example, the participants judged the conditional, If Maria had pneumonia then she was ill , to be true a priori.…”
Section: The Theory Of Mental Modelsmentioning
confidence: 60%
“…We corroborated the possibility table's assignments in the previous study in which the participants judged conditionals as true or false, and we evaluated each of the four cases in their partitions as possible or impossible (Quelhas et al., ). For example, the participants judged the conditional, If Maria had pneumonia then she was ill , to be true a priori.…”
Section: The Theory Of Mental Modelsmentioning
confidence: 60%
“…Hence, interpretation cannot be truth functional (Johnson-Laird & Byrne, 2002). This claim is corroborated in the finding that people judge the not-A cases as possible not only for conditionals that are true a priori, but also for conditionals that are false a priori (Quelhas, Rasga, & Johnson-Laird, 2017). For example, the case of not-A and C is judged possible both for the true conditional, If Pat is reading the article then Pat is alive, and also for the false conditional, If Pat is reading the article then Pat is dead.…”
Section: Introductionmentioning
confidence: 85%
“…Johnson‐Laird and Byrne () accordingly distinguished between everyday conditionals and material implications (p. 655), and they rejected the notion that conditionals have any sort of truth‐functional meaning (p. 673). Likewise, the fact that cases in which the if ‐clause is false are possible for both true and false conditionals is also contrary to material implication (Quelhas et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Prediction 1: when a disjunction refers to the same possibilities as those in knowledge, participants tended to judge that the disjunction was true; when it refers to possibilities that conflict with those in knowledge, they tended to judge that it was false; and otherwise, they tended to judge that is impossible to determine whether it is true or false, that is, it is contingent. These judgments of truth‐value showed that the existence of assertions that are true (and that are false) on the basis of their meanings or knowledge is no longer an unempirical dogma (contrary to Quine, ), and that it is no longer restricted to the special case of conditionals (Quelhas et al, ), because it occurs with disjunctions too. However, as predicted, true judgments included illusory ones for disjunctions that in fact are contingent.…”
Section: Discussionmentioning
confidence: 99%
“…to be false (Quelhas, Rasga, & Johnson‐Laird, ). But proponents of the probabilistic approach to reasoning argue that conditionals are exceptional: They differ in meaning from their counterparts in classical logic, whereas other compounds such as disjunctions do not (e.g., Evans & Over, ; Oaksford & Chater, ).…”
Section: Introductionmentioning
confidence: 99%